Comparison of clinical outcomes in patients with acute ischemic stroke who underwent endovascular treatment using different perfusion modalities: a real-world multicenter study - Gao, Jiali; Jing, Zhen; Huang, Shengming; Yang, Jiajie; Guan, Min; Zhang, Shijun; Li, Hao; Li, Yongxin; Lu, Kui; Yang, Ming; Huang, Li’an (Frontiers in Neurology, 2023)
Background Advanced perfusion modalities are increasingly popular for various diseases. However, few studies have focused on contrasting perfusion patterns. Objective This study aimed to compare the time efficiency and clinical outcomes of patients with acute ischemic stroke (AIS) who underwent endovascular treatment (EVT) before one-stop arterial spin labeling (ASL) and computed tomography perfusion (CTP) protocols. Methods This study retrospectively included 326 patients with AIS who had accepted EVT within 24 h of onset from four comprehensive stroke centers between October 2017 and September 2022. After 1:1 matching of the propensity scores, 202 patients were separated into two groups: the ASL group (n = 101) and the CTP group (n = 101). Results Functional independence at 90 days (modified Rankin Scale [mRS] 0–2; p = 0.574), onset-to-puncture time (p = 0.231), door-to-puncture time (p = 0.136), and door-to-perfusion time (p = 0.646) were not significantly different between the two groups. The proportion of EVT complications (31.7% in the ASL group vs. 14.9% in the CTP group, p = 0.005) and symptomatic intracranial hemorrhage (sICH) at 24 h (23.8% in the ASL group vs. 9.9% in the CTP group, p = 0.008) in the CTP group were lower than the ASL group. The ischemic core volume was a common predictor of favorable outcomes in both ASL (p < 0.001) and CTP (p < 0.001) groups. Conclusion There were no significant differences in time efficiency and efficacy outcomes between the two groups of patients receiving one-stop ASL and CTP. The proportion of sICH at 24 h and EVT complications of patients in the CTP group was lower than the ASL group. The ischemic core volume was an independent predictor for favorable outcomes.